Hyperbaric Storage at Subzero Temperature – the Effect on the Shelf-Life and Selected Quality Characteristics of Raw Pork Sausages - Edyta Malinowska-Pańczyk; Katarzyna Mazur (Polish Journal of Food and Nutrition Sciences)
The aim of this study was to determine the microbiological stability and changes occurring in selected physicochemical properties of raw pork sausages during hyperbaric storage at subzero temperature (HS-ST). It was shown that storage at moderate pressures (up to 111 MPa) led to a reduction in microbial populations. After 21 days of storage under these conditions, no microorganisms were detected in the samples. Additionally, the inhibition of thiobarbituric acid reactive substance (TBARS) formation was observed under HS-ST conditions. The negative effect of the storage at 111 MPa/−10℃ was the sausage colour change from pink to grey-pink or grey, visible to the naked eye. Such changes did not occur in the samples stored at 60 MPa/−5℃ for 35 days. The results showed that applying HS-ST at 60 MPa/−5℃ allowed the shelf-life of raw pork sausages to be effectively extended by at least 35 days without visible quality deterioration.